Sosiolinguistik (Campur Kode Masyarakat Kampung Arab Gorontalo) - Adam, Abdul Azis; Yasin , Zohra; Hairuddin, Hairuddin; Sarif, Suharia (ELOQUENCE : Journal of Foreign Language, 2022)
Background: Code Mixing is a sociolinguistic phenomenon and is common in bilingual or multilingual societies. Purpose: The purpose of this study is to describe the sociolinguistic phenomenon of code-switching through the speech of the Gorontalo Arab community. Method: This research uses a qualitative method to descript the object of code-mixing according to the actual situation and phenomenon. Data collection was done by direct observation with note-taking techniques and interviews with five descendants of Yemeni Hadrami Arab ethnic living in Gorontalo. Results and Discussion: This study concludes that in the speech of ethnic Arabs of Gorontalo Arab Village, there is a code mix in the form of word insertion from Indonesian to Arabic. This study found an external code mix that is often used in the speech of people who live in Gorontalo Arab village, with as much as 25 data. Conclusion and Implication: The results of this study imply that sociolinguistics can be a means of language learning. However, from the grammatical aspect, it has shortcomings due to mixing words that do not follow the standard rules in the two mixed languages. It is believed that there are still many vocabularies that are mixed between Arabic and Indonesian and are often spoken by the Arab community in Gorontalo. Therefore, this research can be developed in a larger population, especially in ethnic Arabs inhabiting several Gorontalo Province areas.